Cost analysis of pulmonary lobectomy procedure: comparison of stapler versus precision dissection and sealant [Corrigendum] - Droghetti A; Marulli G; Vannucci J; Giovanardi M; Bottoli MC; Ragusa M; Muriana G (Dove Medical Press, 2018)
Droghetti A, Marulli G, Vannucci J, et al. Clinicoecon Outcomes Res. 2017;9:201–206. On page 205, Acknowledgments section, “This research was funded by an unrestricted grant from Takeda Italia Spa. We are grateful for the collaboration and support of the Administration of Carlo Poma Hospital, Italy” should have been “We are grateful for the collaboration and support of the Administration of Carlo Poma Hospital, Italy”.Read the original article